a Transformasi Pelayanan Publik Berbasis Artificial Intelligence (AI) guna Meningkatkan Pertahanan Negara - Faonaso Harefa; Cecilia F. Harsono (Badan Pendidikan dan Pelatihan Kementerian Pertahanan, 2025)
This article discusses the importance of the transformation of artificial intelligence-based public services (AI) faced with the development of technology and the demands of the community for public services by the bureaucrats/fast employees, service automation without bureaucrats, faster decision-making, increasing transparency, and optimizing resource management for optimal defense. This research is qualitative research, triangulation data collection techniques, research instruments are researchers as instruments, qualitative descriptive data, informants are 3 public administration experts from Unpas and 17 students of the Pasundan University of Bandung's Doctoral Program. The results showed that the application of AI in public services greatly contributed as the main tool for employees/bureaucrats in the Ministry of Defense in improving public services in the defense sector. This research provides an original value by connecting the idea of ​​public administration digital transformation by increasing national defense, which is still rare discussed thoroughly in academic literature. Therefore, the use of AI increases the efficiency of public services and helps build a defense system that is more resistant to contemporary threats. Limitation of time, funds, and research objects that are not all sub-satker in the Ministry of Defense becomes the observation of researchers so that the results of this study may still be imperfect.